Peripheral nerves modulate the peri-implant osteogenesis under type 2 diabetes through exosomes derived from schwann cells via miR-15b-5p/Txnip signaling axis - Yingying Wang; Fang Qu; Yaqin Wu; Kengliang Lan; Yingyi Shen; Ziang Wu; Qi Zhong; Ximeng Cao; Zhen Fan; Chun Xu (Journal of Nanobiotechnology)
Abstract Studies have shown that the prognosis of dental implant treatment in patients with diabetes is not as good as that in the non-diabetes population. The nerve plays a crucial role in bone metabolism, but the role and the mechanism of peripheral nerves in regulating peri-implant osteogenesis under Type 2 diabetes mellitus (T2DM) situation remains unclear. In this study, it was shown that high glucose-stimulated Schwann cells (SCs) inhibited peri-implant osteogenesis via their exosomes. SCs-derived exosomes were analyzed for their miRNA cargo, identifying miR-15b-5p as significantly downregulated in high glucose conditions. T2DM rats and patients exhibited decreased miR-15b-5p expression, correlating with impaired bone microarchitecture. Luciferase assays and Western blotting confirmed TXNIP as a direct miR-15b-5p target, implicating its involvement in ROS signaling and inflammation-related osteogenesis suppression. Furthermore, normal SCs exosomes improved bone parameters around dental implants in T2DM rats. These findings underscore the therapeutic potential of miR-15b-5p and normal SCs exosomes in mitigating poor peri-implant bone regeneration of T2DM patients, offering insights into the molecular mechanisms of peripheral nerves governing bone regeneration in diabetic conditions. Graphical Abstract